2009
DOI: 10.1093/humrep/dep084
|View full text |Cite
|
Sign up to set email alerts
|

The optimal timing of an ultrasound scan to assess the location and viability of an early pregnancy

Abstract: The ability to confirm viability or non-viability is significantly related to gestational age. In asymptomatic women with no previous ectopic pregnancy TVS should be delayed until 49 days. Our data suggest that this would reduce the number of inconclusive scans, without an associated increase in morbidity from missed ectopic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 20 publications
1
40
0
1
Order By: Relevance
“…Patients seen with or without symptoms and labelled as PUL were 112 (11.6%). 7 Depending upon the risk factors and clinical examination, individual assessment of the patient may reduce morbidity and mortality. Our study observed the outcome of the patients who presented with amenorrhea, bleeding per vaginum and pain abdomen in first trimester and initially labeled as having PUL.…”
Section: Resultsmentioning
confidence: 99%
“…Patients seen with or without symptoms and labelled as PUL were 112 (11.6%). 7 Depending upon the risk factors and clinical examination, individual assessment of the patient may reduce morbidity and mortality. Our study observed the outcome of the patients who presented with amenorrhea, bleeding per vaginum and pain abdomen in first trimester and initially labeled as having PUL.…”
Section: Resultsmentioning
confidence: 99%
“…The majority had a second more powerful reason of needing reassurance (Figs 6 and 7). 13 Here, it is necessary to point out that in our population, a huge emphasis is put on reproduction. This is reflected in that 90% of these patients knew their exact last menstrual period and only 7% have ever used contraception.…”
Section: Discussionmentioning
confidence: 99%
“…US should be deferred for these early presenters, particularly if they are asymptomatic. This is to avoid the conundrum of not being able to confi rm any of the objectives mentioned before and having to repeat the study (Bottomley et al 2009 ).…”
Section: Assessment Of Viabilitymentioning
confidence: 99%